Studi Karakteristik Marshall Pada Campuran Aspal Dengan Penambahan Limbah Botol Plastik - Suhardi, Suhardi; Pratomo, Priyo; Ali, Hadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This experiment aims to investigate the Marshall characteristics due to the variation addition of PET (Polyethylene Terephthalate) at mixtures AC-BC (Asphalt Concrete-Binder Course) finely graded with reference to the specification of Bina Marga 2010. From the result of aalysis has obtained the values of Marshall parameters, the value of the 1 st object groups test and 2nd object groups test, for the parameters marshall meets the specifications already determined by the Bina Marga 2010 on the asphalt level range 6.38% up 6.5%, and the optimum bitumen content value has been obtained is 6.44%. This research proves that with the addition of variations of PET (Polyethylene Terephthalate) in a mixture of AC-BC (Asphalt Concrete-Binder Course) was affected to the Marshall characteristics, as high as the levels of addition PET (Polyethylene Terephthalate) so the value of stability will increase but the percentage of the value of void content in the mix will be higher. Keywords: AC-BC(Asphalt Concrete-Binder Course), Marshall, PET(Polyethylene Terephthalate)